The high molecular weight glutenin subunit Bx7 allergen from wheat contains repetitive IgE epitopes. Issue 10 (2nd August 2014) - Baar, A.; Pahr, S.; Constantin, C.; Giavi, S.; Papadopoulos, N. G.; Pelkonen, A. S.; Mäkelä, M. J.; Scheiblhofer, S.; Thalhamer, J.; Weber, M.; Ebner, C.; Mari, A.; et al.
Abstract Background Wheat is one of the most common food allergen sources for children and adults. The aim of this study was to characterize new wheat allergens using an IgE discovery approach and to investigate their IgE epitopes. Methods A cDNA expression library representing the wheat transcriptome was constructed in phage lambda gt11 and screened with IgE antibodies from wheat food allergic patients. IgE‐reactive cDNA clones coding for portions of high molecular weight (HMW) glutenin subunits were identified by sequence analysis of positive clones. IgE epitopes were characterized using recombinant fragments from the HMW Bx7 and synthetic peptides thereof for testing of allergic patients' sera and in basophil degranulation assays. Results We found that the major IgE‐reactive areas of HMW glutenins are located in the repetitive regions of the protein and could show that two independent IgE‐reactive fragments from HMW Bx7 contained repetitive IgE epitopes. Conclusions Our results demonstrate that IgE antibodies from wheat food allergic patients can recognize repetitive epitopes in one of the important wheat food allergens. Recombinant HMW Bx7 may be included into the panel of allergens for component‐resolved diagnosis of wheat food allergy.